IDENTIFIKASI EKTOPARASIT PADA IKAN KERAPU LUMPUR (Epinephelus coioides) DI KERAMBA JARING APUNG TAPIAN NAULI, KABUPATEN TAPANULI TENGAH - Sri Wahyuni Pasaribu; Eddiwan Eddiwan; Anne Rumondang; Fiki Harjuni; Henny Syawal (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
The purpose of this study was to identify and determine the prevalence, intensity, and dominance of ectoparasites in mud grouper (Epinephelus coioides). This study was conducted in August - November 2023. Sampling was carried out in Tapian Nauli Floating Net Cages, Central Tapanuli Regency, while ectoparasite identification was carried out at the Fish Health Laboratory, Matauli Fisheries and Marine College. Sampling was conducted using purposive sampling of fish showing clinical signs of illness. Data obtained from the results of parasite identification and analyzed descriptively and presented in the form of figures and tables. The results showed that 2 types of ectoparasites were found in mud grouper fish kept in floating net cages, Tapian Nauli, Central Tapanuli, namely Dactylogyrus sp. and Trichodina sp. The prevalence of Dactylogyrus sp. in all cages was 14.4% and Trichodina sp. 1.11% while the intensity and dominance of each ectoparasite are; 26 individuals/each (90.72%) and 5 individuals/each (1.33%). The water quality values ​​during sampling were temperature of 27.1 oC - 29.8 oC, pH of 6.7 - 7.1, DO of 5.2 ppm - 6.6 ppm, salinity of 20 ppt - 28 ppt, and the weather was cloudy, drizzle, and light rain.